Neither Cold nor Hot - Ian Roberge; Daven Ng (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2025)
This paper is interested in hybrid warfare and states’ defensive policy responses from a Western perspective. Hybrid warfare has become a critical component of contemporary interstate conflicts, deliberately narrowing the gap between conventional military engagements and grey zone operations. It combines military tactics with non-military tools, such as cyber operations, disinformation campaigns, and economic coercion, to weaken adversaries without engaging in conventional warfare. Russia’s War in Ukraine illustrates the use of hybrid warfare to achieve imperialist objectives, while similar campaigns have targeted other Western democracies. China’s actions in the Indo-Pacific reflect comparable hybrid strategies. While much attention has focused on its offensive use, less is known about how states respond defensively. This paper explores how Australia, New Zealand, the United Kingdom, Canada, the United States, and Finland respond to hybrid threats. It argues that Western policy responses are uneven, with some states better prepared than others. Effective defence requires a clear definition of hybrid warfare, a whole-of-government approach, and sustained resources. Based on publicly available policy documents, this comparative case study assesses how national interests are protected, despite limitations due to the classified nature of hybrid operations.